Análisis de las propuestas de reactivación económica para el sector turístico de Manabí, post 16 A. - Loor Zambrano, Yoselin Melissa (2018)
The analysis of the proposals for the economic reactivation of Manabí tourist sector, post 16 a, was aimed at assessing the level of progress of tourism associations and their activities. For this, we proceeded to the search of bibliographic information, that represent the socioeconomic tourist situation of Manabí. We proceeded to carry out the sampling for convenience, being determined Pedernales canton. The interview guide was elaborated to apply it to the quality informants, and likewise, the questionnaire was designed to carry out the surveys to the tourists that come to the different zones, as well as a focal group to the associations of the canton dedicated to tourist activities; these instruments together served as a method to know the conditions they currently experience, such as the decrease in income by 40%, the decrease in hotel beds, and the 4% acceptance of financial loans. Once the result was obtained, the influence of the environments was carried out using the PEST matrix, and as a last point, a critical analysis was carried out through the matrix of success criteria, analyzing the proposals made and diagnosing the current situation of the groups that belong to the tourism sector, determining on this basis the level of progress in the reactivation, in addition to showing and capturing the factors that have impeded their potential, contributing with specific data for the development of strategies that tend to improve said nonconformities.